Assessment of Myocardial Bridge and Mural Coronary Artery Using ECG-Gated 256-Slice CT Angiography: A Retrospective Study. (20th May 2013) - Ma, En-sen; Ma, Guo-lin; Yu, Hong-wei; Wu, Wang; Li, Kefeng
Abstract : Recent clinical reports have indicated that myocardial bridge and mural coronary artery complex (MB-MCA) might cause major adverse cardiac events. 256-slice CT angiography (256-slice CTA) is a newly developed CT system with faster scanning and lower radiation dose compared with other CT systems. The objective of this study is to evaluate the morphological features of MB-MCA and determine its changes from diastole to systole phase using 256-slice CTA. The imaging data of 2462 patients were collected retrospectively. Two independent radiologists reviewed the collected images and the diagnosis of MB-MCA was confirmed when consistency was obtained. The length, diameter, and thickness of MB-MCA in diastole and systole phases were recorded, and changes of MB-MCA were calculated. Our results showed that among the 2462 patients examined, 336 have one or multiple MB-MCA (13.6%). Out of 389 MB-MCA segments, 235 sites were located in LAD2 (60.41%). The average diameter change of MCA in LAD2 from systole phase to diastole phase was 1.1 ± 0.4  mm, and 34.9% of MCA have more than 50% diameter stenosis in systole phase. This study suggested that 256-slice CTA multiple-phase reconstruction technique is a reliable method to determine the changes of MB-MCA from diastole to systole phase.